2007
DOI: 10.1017/s1355617707071317
|View full text |Cite
|
Sign up to set email alerts
|

Dexamphetamine boosts naming treatment effects in chronic aphasia

Abstract: To date, minimal research has investigated the effect of combining dexamphetamine with standard naming therapy after stroke. The present study used a double-blind, placebo-controlled, multiple baseline, crossover design with two individuals in the chronic stage of stroke recovery. Each individual attended two 4-week blocks of naming therapy (two to three treatment sessions per week). Dexamphetamine (10 mg) was administered at the start of each session during one therapy block, while a placebo was administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Some improvement in naming has been reported using cholinergic (neurotransmitter therapy) and bromocriptine (a dopaminergic agent; National Aphasia Organization). A promising result was reported for dexamphetamine combined with speech therapy (Whiting, Chenery, Chalk, & Copland, 2007) in the treatment of chronic aphasic naming errors.…”
Section: Discussionmentioning
confidence: 99%
“…Some improvement in naming has been reported using cholinergic (neurotransmitter therapy) and bromocriptine (a dopaminergic agent; National Aphasia Organization). A promising result was reported for dexamphetamine combined with speech therapy (Whiting, Chenery, Chalk, & Copland, 2007) in the treatment of chronic aphasic naming errors.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamphetamine, a drug with psychoactive properties that inhibits the reuptake of dopamine and norepinephrine (Walker-Batson et al 1992;McNeil et al 1997;Whiting et al 2008), has been used to alleviate motor and language deficits in stroke patients (Walker-Batson et al 1992;McNeil et al 1997;Whiting et al 2008). The effects of dexamphetamine administered every third or fourth day and paired with 1-h session of SLT seem to be stronger during the acute recovery process, possibly by accelerating the resolution of diaschisis and enhancing plasticity of behaviorally stimulated networks (Walker-Batson et al 2001;Hillis 2007;Small and Llano 2009).…”
Section: Catecholaminergic Drugsmentioning
confidence: 99%
“…The effects of dexamphetamine administered every third or fourth day and paired with 1-h session of SLT seem to be stronger during the acute recovery process, possibly by accelerating the resolution of diaschisis and enhancing plasticity of behaviorally stimulated networks (Walker-Batson et al 2001;Hillis 2007;Small and Llano 2009). Studies on chronic PSA are scant and provide divergent outcomes, with benefits only obtained when dexamphetamine was paired with intensive naming therapy (Whiting et al 2008), but lack of effect was reported in another trial using a similar methodology (McNeil et al 1997). Thus, although larger clinical trials in PSA may be justified (Goldstein 2009), at present dexamphetamine is not recommended in clinical practice (Martinsson and Eksborg 2004;Floel and Cohen 2010).…”
Section: Catecholaminergic Drugsmentioning
confidence: 99%
“…Amphetamine inhibits the reuptake of dopamine and norepinephrine. Though, there are studies which used amphetamine to investigate the drug effectiveness on aphasia which have proved to be helpful when accompanied with intensive speech and language therapy (105,106), still they are not recommended for the treatment of aphasia in clinics (107).…”
Section: Drugs Acting On Catecholaminergic Systemmentioning
confidence: 99%